2017
DOI: 10.1093/eurpub/ckx148
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum bisphenol A levels and risk of pre-eclampsia: a nested case–control study

Abstract: BackgroundAlthough recent studies have indicated the potential adverse effects of maternal bisphenol A (BPA) exposure on pregnancy such as increasing the risk of pre-eclampsia, epidemiological evidence is limited. We aimed to evaluate the relationship between maternal BPA exposure and the risk of pre-eclampsia. MethodsWe conducted a nested case–control study among 173 women (74 cases of pre-eclampsia and 99 controls). BPA concentrations were measured using liquid chromatography-mass spectrometry in the materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Previous studies showed that BPA exposure affects placental angiogenesis and morphology in mice . Studies have demonstrated a positive correlation between risk of PE‐like features such as disruption of the circulation or hypertension and maternal exposure to BPA and also studies have proven altered global DNA methylation levels in mice placentas of BPA exposed . WNTs signaling has an important role in trophoblast invasion but BPA exposure during pregnancy prevented placental spiral artery remodeling and trophoblast invasion .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“…Previous studies showed that BPA exposure affects placental angiogenesis and morphology in mice . Studies have demonstrated a positive correlation between risk of PE‐like features such as disruption of the circulation or hypertension and maternal exposure to BPA and also studies have proven altered global DNA methylation levels in mice placentas of BPA exposed . WNTs signaling has an important role in trophoblast invasion but BPA exposure during pregnancy prevented placental spiral artery remodeling and trophoblast invasion .…”
Section: Epigenetic Changes In Pementioning
confidence: 99%
“…During this period, hormone and protein levels will change and balance as cells begin to grow and differentiate. When EDCs are transferred into the fetus through the placenta, the equilibrium state of the hormonal environment will be broken, due to the sensitivity of the immature fetus to EDCs, resulting in miscarriage, fetal growth retardation, and preeclampsia [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…BPA is detectable in the urine, serum, and placental tissues of pregnant women (11). Epidemiologic studies have reported a positive association between maternal exposure to BPA and the risk of preeclampsia (9,10,13). BPA exposure also affects placental morphology and angiogenesis during early pregnancy in mice (7), and the WNT2 signaling pathway may be involved (7).…”
mentioning
confidence: 99%
“…Epigenetic regulation is vital during placental development, and abnormal epigenetic regulation in the placenta is associated with preeclampsia (15). Although mounting data suggest a positive correlation between BPA exposure and preeclampsia (6,7,9,10,13), evidence confirming a causal relationship is currently unavailable.…”
mentioning
confidence: 99%